Incidental Tuberculosis in sudden, unexpected, and violent deaths in the community Lusaka, Zambia - A descriptive forensic post-mortem examination study. (November 2022) - Mucheleng'anga, Luchenga Adam; Himwaze, Cordilia M.; Telendiy, Viktor; Simumba, Suzyani; Soko, Jonathan; Kayonde, Nathan; Mulenga, Bwalya; Hamukale, Amos; Shibemba, Aaron Lunda; Lungu, Patrick S.; Tembo, John; Bates, Matthew; et al.
Highlights: Forensic autopsies of community deaths show incidental, undiagnosed TB cases Undiagnosed TB and related deaths reveal gaps in TB control programs TB remains an important public health problem in Lusaka, Zambia Low social-economic status and TB are intertwined in these cases ABSTRACT: Objectives: Tuberculosis remains a global emergency. In Zambia only 55% of tuberculosis cases are diagnosed. We performed a study to determine incidental cases of tuberculosis seen at forensic autopsy of individuals who died suddenly and unexpectedly in the community in Lusaka, Zambia. Methods: Whole-body autopsies were performed according to Standard Operating Procedures. Representative samples obtained from relevant organs were subjected to pathological examination. Information on circumstances surrounding the death was obtained. Data on patient demographics, gross and microscopic pathological findings, and cause(s) of death were analysed. Results: Incidental tuberculosis was found in 52 cases (45 male, 7 female, age range 14-66) out of 4286 whole-body autopsies. 41/52 (80%) were aged 21-50 years. One was a 14-year old boy who died during a football match. 39/52 (75%) deaths were attributable specifically to tuberculosis only. Other deaths were due to acute alcohol intoxication(4), violence(7), ruptured ectopic pregnancy(1), bacterial meningitis (1). All the cases were from poor socio-economic backgrounds and lived in high-density areas of Lusaka. Conclusions: Incidental cases of active tuberculosis undiagnosed antemortem seen at forensic autopsy reflects major gaps in the national TB control programs. More investments into proactive screening, testing, treatment activities, and accurate data collection are required.